2021
DOI: 10.1155/2021/5595047
|View full text |Cite
|
Sign up to set email alerts
|

Lead‐Induced Motor Dysfunction Is Associated with Oxidative Stress, Proteome Modulation, and Neurodegeneration in Motor Cortex of Rats

Abstract: Lead (Pb) is a toxic metal with great neurotoxic potential. The aim of this study was to investigate the effects of a long-term Pb intoxication on the global proteomic profile, oxidative biochemistry and neuronal density in motor cortex of adult rats, and the possible outcomes related to motor functions. For this, Wistar rats received for 55 days a dose of 50 mg/Kg of Pb acetate by intragastric gavage. Then, the motor abilities were evaluated by open field and inclined plane tests. To investigate the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In the last years, we have shown that xenobiotics such as mercury, lead, and fluoride, have an interesting ability to modulate the proteostasis system [ 52 , 53 , 66 , 67 ]. One complex involved in proteostasis is the ubiquitin-proteasome, which regulates the degradation of proteins, along with the Heat Shock Proteins (HSP), which also work on the degradation process, but have special functions in preventing the misfolding of proteins that could lead to the formation of protein aggregates [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, we have shown that xenobiotics such as mercury, lead, and fluoride, have an interesting ability to modulate the proteostasis system [ 52 , 53 , 66 , 67 ]. One complex involved in proteostasis is the ubiquitin-proteasome, which regulates the degradation of proteins, along with the Heat Shock Proteins (HSP), which also work on the degradation process, but have special functions in preventing the misfolding of proteins that could lead to the formation of protein aggregates [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic data analyses were only possible due to the comparability between the samples within the same group, and the use of Protein Lynx GlobalSERVER software, robust software for data analyses, was able to determine the p values, hence the quantitative proteomic analysis, considering p < 0.05 for downregulated proteins and 1 − p > 0.95 for upregulated proteins. Detailed methodology is available elsewhere [ 11 , 66 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that Pb is a neurotoxicant that can cause impaired motor function, behavioral dysfunction, and cognitive decline in humans and rats (5)(6)(7). Chronic exposure to Cd is associated with various adverse effects including memory loss, motor neuron disease, behavioral changes, delayed psychomotor activity in workers (8)(9)(10), and impaired memory and learning in experimental animals (11).…”
Section: Introductionmentioning
confidence: 99%